ON-GRID AND OFF-GRID RENEWABLE ENERGY DESIGN AS SWRO (SEAWATER REVERSE OSMOSIS) POWER FOR FRESHWATER NEEDS IN GILI TRAWANGAN (STUDI CASE: GILI TRAWANGAN) - Robbani, Farisan; Ridwan, Mohammad Kholid; Darmawan, Arif (ASEAN Journal of Systems Engineering, 2025)
Indonesia has 17,504 islands and one of them is Gili Trawangan. Gili Trawangan is one of the favorite tourist destinations in Indonesia which has an area of approximately 6 km2. In order to achieve the development of tourism islands, sufficient water and energy are needed in the area. The island's location in the middle of the sea makes it difficult to get freshwater and energy supplies.In this study, on-grid and off-grid simulations of renewable energy (solar, wind, and biomass) were carried out to determine the potential of integration energy as seawater desalination power as the need for freshwater in the area by calculating NPC (Net Present Cost), COE (Cost of Energy), operational costs, energy, and CO2 emissions. In the off-grid simulation, the lowest NPC and COE integration potentials were found at PV (Photovoltaic) capacities of 102 kW, 14 WT (Wind Turbine), 50 kW BG (Biogas Generator), and 50 kW DG (Diesel Generator) with a value of Rp 17,042,910,000 and Rp 1,587. The lowest operational costs and CO2 emissions are at the PV capacity of 209 kW, 8 WT, 50 kW BG, and 50 kW DG with a value of Rp 292,308,100 and 163 kg/year. In energy production, there is excess production and electrical energy at the PV capacity of 188 kW, 25 WT, 50 kW BG, and 50 kW DG with values of 2,301,533 kWh/year and 1,821,626 kWh/year. On-grid simulation results obtained the lowest NPC and NOE at 30 kW PV, 5 WT, and 50 kW BG with a value 2,961,782,000 and Rp. 200. Lowest operating costs, lowest CO2 emissions, largest electricity production, and best electricity trading at the PV capacity of 209 kW, 5 WT, and 50 BG with a value Rp 12,428,750, 84,000 kg/year, 882,455 kWh/year, 239,996 kWh, and 132,911 kWh.